2021
DOI: 10.1002/ece3.7970
|View full text |Cite
|
Sign up to set email alerts
|

An approach to rapid processing of camera trap images with minimal human input

Abstract: Camera traps have become an extensively utilized tool in ecological research, but the manual processing of images created by a network of camera traps rapidly becomes an overwhelming task, even for small camera trap studies. We used transfer learning to create convolutional neural network (CNN) models for identification and classification. By utilizing a small dataset with an average of 275 labeled images per species class, the model was able to distinguish between species and remove false triggers. We trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We calculated three metrics to evaluate our model performance at correctly identifying species (e.g. Duggan et al 2021). Specifically, we relied on accuracy the ratio of correct predictions to the total number of predictions, recall a measure of false negatives (FN; e.g.…”
Section: Training -Jura Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…We calculated three metrics to evaluate our model performance at correctly identifying species (e.g. Duggan et al 2021). Specifically, we relied on accuracy the ratio of correct predictions to the total number of predictions, recall a measure of false negatives (FN; e.g.…”
Section: Training -Jura Study Sitementioning
confidence: 99%
“…an image with any species but a lynx for which our model predicts a lynx) with precision = TP / (TP + FP). In camera trap studies, a strategy (Duggan et al 2021) consists in optimizing precision if the focus is on rare species (lynx), while recall should be optimized if the focus is on commom species (chamois and roe deer).…”
Section: Training -Jura Study Sitementioning
confidence: 99%
“…Within the context of sensor-based assessment method, data are massive and needs to be processed before being analyzed. This consists in identifying the taxon of interest in a large amount of collected data, referred to as identification or classification, which can be carried out either manually by one or several operators (Swanson et al, 2015; Welbourne et al, 2015), either automated using deep learning algorithms (Duggan et al, 2021; Tabak et al, 2019), or a combination of both (Augustine et al, 2023; Campos-Cerqueira and Aide, 2016). For images and acoustic data, combining manually and automatically-generated data processing helps to control classification errors; when one species is mistaken for another (Barré et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the considerable time and effort expended by researchers when classifying camera trap images, many studies have deployed the use of machine learning to rapidly classify animal species and anthropogenic objects, including humans and vehicles (Duggan et al, 2021 ; Tabak et al, 2018 ). In fact, some studies have even found that machine‐learning models can sometimes outperform the average citizen scientist with regard to accuracy (Norouzzadeh et al, 2018 ; Whytock et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%